What’s up doc? A national cross-sectional study of psychological wellbeing of hospital doctors in Ireland - Hayes, Blánaid (BMJ Open, 2017)
OBJECTIVES: To measure levels of psychological distress, psychological wellbeing and self-stigma in hospital doctors in Ireland. DESIGN: National cross-sectional study of randomised sample of hospital doctors. Participants provided sociodemographic data (age, sex, marital status), work grade (consultant, higher/basic specialist trainee), specialty and work hours and completed well-being questionnaires (the Depression Anxiety Stress Scale, WHO Well-being Index, General Health Questionnaire) and single-item scales on self-rated health and self-stigma. SETTING: Irish publicly funded hospitals and residential institutions. PARTICIPANTS: 1749 doctors (response rate of 55%). All hospital specialties were represented except radiology. RESULTS: Half of participants were men (50.5%). Mean hours worked per week were 57 hours. Over half (52%) rated their health as very good/excellent, while 50.5% reported positive subjective well-being (WHO-5). Over a third (35%) experienced psychological distress (General Health Questionnaire 12). Severe/extremely severe symptoms of depression, anxiety and stress were evident in 7.2%, 6.1% and 9.5% of participants (Depression, Anxiety, Stress Scale 21). Symptoms of distress, depression, anxiety and stress were significantly higher and levels of well-being were significantly lower in trainees compared with consultants, and this was not accounted for by differences in sociodemographic variables. Self-stigma was present in 68.4%. CONCLUSIONS: The work hours of doctors working in Irish hospitals were in excess of European Working Time Directive’s requirements. Just over half of hospital doctors in Ireland had positive well-being. Compared with international evidence, they had higher levels of psychological distress but slightly lower symptoms of depression and anxiety. Two-thirds of respondents reported self-stigma, which is likely to be a barrier to accessing care. These findings have implications for the design of support services for doctors, for discussions on quality of patient care and for future research.